Relationship Between Interpersonal Skills, Emotional Intelligence And Managerial Performance At Indah Water Konsortium Sdn Bhd - Kanthasamy, Abiramee (2009)
Every manager has that something special that makes them most effective as a manager of people and a leader in an industry. When a manager can identify their strengths, they can use that to effectively inspire their employees, enhance their managerial performance and create a healthy working environment. Managers today have to handle issues pertaining to performance objectively and decisively, as well as to provide their employees, feedback on a regular basis and guidance in order to assist them in improving their performance. Hence, this study attempts to examine the relationship of interpersonal skills, emotional intelligence as well as the moderating effect of the manager's organizational commitment towards their performance. This study involves a questionnaire based survey of selected 1 00 managerial staffs from Indah Water Konsortium Sdn Bhd. The frequency analysis, factor analysis, reliability test and hierarchical regressions analysis was used to analyze the results of the research.